Pilonidal Sinus Disease: A 10-Year Review Reveals Occupational Risk Factors and the Superiority of the Minimal Surgery Trephine Technique. Issue 4 (1st April 2016) - Levinson, Tal; Sela, Tamar; Chencinski, Shmuel; Derazne, Estela; Tzur, Dorit; Elad, Hadar; Kreiss, Yitshak
ABSTRACT: Objectives: To identify military occupational risk factors for pilonidal sinus disease (PSD) and to compare an Army Clinic minimal surgery with techniques used at public hospitals. Methods: Review of a historical cohort of soldiers (3, 407 with PSD) to determine PSD risk factors in military personnel and comparison of postoperative sick leave days between surgical techniques. Results: Male and female officers had a lower PSD incidence, whereas male combatants and female drivers were at higher risk compared to administrative personnel. The minimal surgery technique used at the Army Clinic was associated with an average 13 less postoperative sick leave days per patient, as compared to the surgical techniques including wide excision used at public hospitals. Compared to healthy soldiers, the relative risk for PSD recurrence was 7.87 in all males and 9.54 in male combatants. Conclusions: Male combatants and female drivers are at higher risk for PSD, whereas officers and administrative personnel are at lower risk. Compared with surgical techniques used at public hospitals, the Army Clinic exclusive use of the Gips minimal surgery technique is associated with fewer sick leave days. Prior surgery for PSD is a positive predictor of recurrence, and these patients warrant secondary prevention.